Analysis of UN peacekeeping operations in the Democratic Republic of Congo - Kohashi, Asami (Riga Graduate School of Law, 2023)
This research paper aims to analyze the UN Peacekeeping operation in the Democratic Republic of the Congo (MONUSCO) and examine the legal challenges to achieving its mission objectives. Despite long-term international support to the state, human rights violations remain severe, and the government suffers from an unstable legal environment, leading to a question about the necessity of the mission. Doctrinal and empirical research methods demonstrate this study by examining legal norms, cases, and statistics. It argues that three main legal challenges impair MONUSCO’s efficacy: lack of legal instruments for the citizens, non-improvement of human rights violations by the state organs, and limitation on the use of force. As a result, further observation and sustainable assistance are crucial elements for enhancing human rights security in the DRC until there are signs of improvement.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; the United Nations; Peacekeeping operation; State responsibility; State attribution; Democratic Republic of the Congo